Spectrum of Inherited Metabolic Diseases in neonates and children presenting at Izzat Ali Shah Hospital, Wah Cantt. - Lubna Ehtizaz, Shahzad Haider, Zahid Mahmood, Sajid Nazir, Tahira Tehseen, Tahir Mahmood, Lubna Ehtizaz, Shahzad Haider, Zahid Mahmood, Sajid Nazir, Tahira Tehseen, Tahir Mahmood (Journal of Rawalpindi Medical College, 2021)
Objective: To determine the frequency of various Inherited Metabolic Diseases (IMDs) in clinically suspected neonates and children in relation to age, gender, and distribution in rural and urban areas. Materials and Methods: A total of 275 symptomatic neonates and children were enrolled for IMDs. A complete medical history, baseline biochemical tests, cerebrospinal fluid analysis, arterial blood gases, anion gap, serum ammonia, lactate, and urinary ketones were assessed. Any significant microbiological cause for the presenting symptom was excluded. For screening of Inborn Metabolic Error simple Heel prick test was done on PerkinElmer 226 filter paper in newborns and infants. Samples were sent to Jordan for analysis. High-performance liquid chromatography combined with tandem mass spectrometry (LC-MS/MS) was the technique used in the screening of a variety of IMDs. The frequency of Inherited Metabolic Diseases and their relation with age, gender, and location was determined using the chi-square goodness of fit test. A p-value ≤ of 0.05 was considered statistically significant. Results: Of the 275 subjects screened, 47(17%) had an inherited metabolic disorder, of which 27 were male and 20 were female with a Male to Female ratio of 1.35:1. The difference in metabolic disorders was significantly different between age (p=0.01) and gender (p=0.04). Of the diagnosed cases G6PD disorder was found to be the most frequent disorder 14 (29.79%) of the total diagnosed cases, followed by Aminoaciduria in 9 (19.15%) and Carnitine Uptake Defect in 7 (14.8). Conclusion: The cases detected to have IMDs revealed a significant prevalence. G6PD was detected as the most frequent disorder. A simple Heel prick test on PerkinElmer 226 filter paper is a useful method to detect IMDs, though confirmation is usually required by other tests.